Role of biochemistry and cytological analysis of cyst fluid for the differential diagnosis of pancreatic cysts: A retrospective cohort study. Issue 1 (January 2017) - Soyer, Ozlem Mutluay; Baran, Bulent; Ormeci, Asli Ciftcibasi; Sahin, Davut; Gokturk, Suut; Evirgen, Sami; Basar, Rafet; Firat, Pinar; Akyuz, Filiz; Demir, Kadir; Besisik, Fatih; Kaymakoglu, Sabahattin; et al.
Abstract: Background: Management of pancreatic cysts is based on neoplastic–nonneoplastic discrimination. Endoscopic ultrasound (EUS) enables to differentiate neoplastic–nonneoplastic lesions and also allows fine-needle aspiration (FNA). In this study, we aim to assess feasibility and clinical relevance of cytological and biochemical analysis in differential diagnosis of cystic pancreatic lesions in patients who had undergone endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) due to pancreatic cysts. Methods: Participants were 96 patients who had undergone EUS-FNA for differential diagnosis of pancreatic cysts. Pancreatic cysts were classified as benign-mucinous, nonmucinous, and malignant according to patient history, physical examination, EUS appearance, and cystic fluid assessment. Tumor markers (CEA, CA(cancer antigens) 72.4, CA 19-9), amylase, lipase and cytological assesment were compared between 3 different groups. Receiver-operating characteristics (ROC) curves were constructed to identify appropriate cut-off values. Results: Fluid CEA and CA 72.4 levels for benign-mucinous and malignant cysts were significantly higher than for nonmucinous cysts ( P  ≤ 0.04). A cut-off CEA level of 207 ng/mL differentiated mucinous etiology with a sensitivity of 72.7%, specificity of 97.7%, and accuracy of 89.5%. The sensitivity, specificity, and accuracy of the CA 72.4 cut-off level of 3.32 ng/mL were 80%, 69.5%, and 73.6%, respectively. Conclusion: Cyst fluid CEA and CA 72.4 levels have a high accuracy in discriminating mucinous from nonmucinous cysts. When combined with cytology their accuracy rate increases.